CEO Compensation: Evidence from the Field - Alex Edmans; Tom Gosling; Dirk Jenter (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We survey directors and investors on the objectives, constraints, and determinants of CEO pay. 67% of directors would sacrifice shareholder value to avoid controversy on CEO pay, implying they face significant constraints other than participation and incentive compatibility. These constraints lead to lower pay levels and more one-size-fits-all structures. Shareholders are the main source of constraints, suggesting directors and investors disagree on how to maximize value. Respondents view intrinsic motivation and reputation as stronger motivators than incentive pay. They believe pay matters to CEOs not to finance consumption, but because it affects perceptions of fairness. The need to fairly recognize the CEO's contribution explains why flow pay responds to performance, even though CEOs' equity holdings already provide substantial consumption incentives, and why peer firm pay matters beyond retention concerns. Fairness also matters to investors, with shareholder returns an important reference point. This causes CEO pay to be affected by external risks, in contrast to optimal risk sharing.
Keywords: G34; G38; M12; M52; 330; executive compensation; contract theory; CEO incentives; fairness; survey